Aurora Kinase A-YBX1 Synergy Fuels Aggressive Oncogenic Phenotypes and Chemoresistance in Castration-Resistant Prostate Cancer - Nikhil, Kumar (Cancers (Basel), 2020)
Multifunctional protein YBX1 upregulation promotes castration-resistant prostate cancer (CRPC). However, YBX1 protein abundance, but not its DNA status or mRNA levels, predicts CRPC recurrence, although the mechanism remains unknown. Similarly, the mechanism by which YBX1 regulates androgen receptor (AR) signaling remains unclear. We uncovered the first molecular mechanism of YBX1 upregulation at a post-translational level. YBX1 was identified as an Aurora Kinase-A (AURKA) substrate using a chemical screen. AURKA phosphorylates YBX1 at two key residues, which stabilizes it and promotes its nuclear translocation. YBX1 reciprocates and stabilizes AURKA, thereby initiating a synergistic loop. Notably, phospho-resistant YBX1 is dominant-negative and fully inhibits epithelial to mesenchymal transition, chemoresistance, drug-resistance and tumorigenesis in vivo. Unexpectedly, we further observed that YBX1 upregulates AR post-translationally by preventing its ubiquitylation, but not by increasing its transcription as reported before. Uncovering YBX1-mediated AR stabilization is highly significant due to AR’s critical role in both androgen-sensitive prostate cancer and CRPC. As YBX1 inhibitors are unknown, AURKA inhibitors provide a potent tool to degrade both YBX1 and AR simultaneously. Finally, this is the first study to show a reciprocal loop between YBX1 and its kinase, indicating that their concomitant inhibition will be act synergistically for CRPC therapy.